Persepsi Petani Terhadap Budidaya Gandum Tropis - M. Alfian Happy Pramuditya; Tinjung Mary Prihtanti (Agric, 2019)
Indonesia tried to cultivated wheat since 2000. Characteristics of Indonesia as a tropical country caused the productivity of wheat crops was relatively lower than the productivity of sub-tropical wheat cultivation. The development of wheat cultivation was carried out in various regions, including in Central Java Province. Several institutions had participated to introduce the wheat cultivation in Central Java province. This study explores the farmer perceptions on wheat farming and correlation between internal driver and external driver and farmer's perception on wheat farming, and the correlation between farmer perception toward farmer motivation to cultivate wheat. This research used survey technique to collect primary data from farmers who get involved on wheat cultivation introduction program. Data analysis techniques were used rank spearman correlation analysis. The study showed that respondents in Demak Regency tend to have the perception that wheat cultivation is very unprofitable, not easily cultivated and has a high risk of crop failure. Respondents in Boyolali tend to have the perception that wheat is easily cultivated, but has a high risk of crop failure and high selling prices. Respondents in Klaten Regency tend to have the perception that wheat cultivation is not profitable and has a high risk of crop failure, but has a high selling price. There is no significant relationship on age, education, farming experience, frequency of extension, and farm environmental conditions on farmers' perceptions. There are significant relationship between farmer status, land area, with farmers’ perception on wheat cultivation, and the farmers perception had relation with farmers motivation to cultivate wheat